CLASSIFICATION OF CAT AND DOG CONCEPTS - Новікова, Ольга (SWorldJournal, 2022)
The article deals with the study of classifications of linguistic and cultural concepts CAT and DOG as units of the British conceptosphere. In modern linguistics, we see a deep interest in the problems of the relationship between language, consciousness